Fluctuating Asymmetry in Root Number and Morphology of Permanent Premolars and Molars - Case Reports - I. Anand Sherwood; P. Govinda Reddy (Dental Anthropology Association, 2011)
Aim of this article is to report cases with fluctuating asymmetry in root morphology and root number in permanent premolars and molars and to survey the literature about reporting for fluctuating asymmetry in roots of teeth. Fluctuating asymmetry is a left-right asymmetry of a paired structure that is usually symmetrical. Teeth in corresponding quadrants of the upper and lower jaws are normally symmetrical structures that exhibit mirror imagery. Fluctuating asymmetry does occur at varying levels for all root traits. Fluctuating asymmetry for root morphology and number has been poorly studied. In this article, 21 cases with fluctuating asymmetry in root number and morphology of permanent premolars and molars are reported. Key points are: (1) Fluctuating asymmetry seems to be occurring in Tamil speaking population of Madurai South India more frequently than reported for Caucasian populations. (2) More detailed study of variation in root morphology with greater emphasis on fluctuating asymmetry for root morphology is warranted. 3) Fluctuating asymmetry is of importance to clinical dentists, dental morphologists, and dental anthropologists.